Globalisation as a factor of marketing concepts’ evolution - I. V. Alyoshina (Управление)
The research aims to reveal the logic of the marketing concepts’ evolution in the context of globalization processes of the XX–XXI centuries in order to identify the emerging marketing paradigm, meaningful for Russian realities. The globalization of markets, the economy and public life is interpreted as an objective reality determined by scientiﬁc and technological progress. The sequence of four stages in the development of economic globalization has been presented and characterised. Marketing concepts’ evolution of American companies, traditional leaders of world markets, is viewed in the process of unfolding of four-stage evolution of globalization during the last century, determined by a series of industrial revolutions. In the context of the globalization processes development, a comparative description of seven marketing concepts has been given – from improving production to holistic marketing. The sequence of changes of marketing dominants in the Russian Federation since the beginning of market economy development in the 1990s has been presented, – from marketing of import to import-substitution marketing and export-oriented marketing. The research is based on the analysis of sources with overlapping themes of globalisation and marketing, including the ﬁeld of global value networks. The convergence of these areas of knowledge in the process of globalization and of digital markets’ expansion has been noted. The features of the marketing paradigm in the age of digital globalization and its signiﬁcance for the Russian business global positioning and for its business models’ global platformisation have been determined. The conclusion has been made about the importance of the holistic marketing concept for solving the problems of digitalisation of the economy and digital management transformation in the Russian Federation.